Pemberdayaan Remaja Melalui Pengajian Tahsin Dan Pendidikan Agama - Dessy Asnita; Agustinar; Asih Pertiwi; Syarifah Mudrika (Fakultas Ekonomi dan Bisnis Islam - IAIN Lhokseumawe, 2023)
This research seeks to bridge the gap in religious understanding among teenagers through a community service program. The program's focus is on teenagers in Dusun Bukit, Paya Bujuk Seulemak Village, Langsa City, who often face difficulties in comprehending religious and ethical values. The program aims to enhance their understanding of religion, tajwid (Quranic recitation rules), and foster good Islamic character. Over a span of three months, the training program is structured into four phases: introducing the Quran and its virtues, teaching tajwid, imparting religious knowledge, and nurturing Islamic ethics. The results of this community service initiative indicate that the teenagers have experienced improvements in their understanding of the Quran, tajwid, and religious knowledge. They have also displayed developments in their character and Islamic ethics, such as empathy, honesty, patience, and social concern. Despite encountering various challenges, such as conflicting schedules with work or education, the majority of teenagers have remained consistent in their participation. This research demonstrates the significance of community service programs in addressing the lack of religious understanding among teenagers. A strong religious understanding can assist teenagers in facing everyday challenges and in shaping good character. Furthermore, the program highlights the positive impact of involving parents in program activities in terms of increased support and teenage participation.